2016
DOI: 10.1002/2016gl069456
|View full text |Cite
|
Sign up to set email alerts
|

Thermal equation of state of hcp‐iron: Constraint on the density deficit of Earth's solid inner core

Abstract: We conducted high‐pressure experiments on hexagonal close packed iron (hcp‐Fe) in MgO, NaCl, and Ne pressure‐transmitting media and found general agreement among the experimental data at 300 K that yield the best fitted values of the bulk modulus K0 = 172.7(±1.4) GPa and its pressure derivative K0′ = 4.79(±0.05) for hcp‐Fe, using the third‐order Birch‐Murnaghan equation of state. Using the derived thermal pressures for hcp‐Fe up to 100 GPa and 1800 K and previous shockwave Hugoniot data, we developed a thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
160
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(187 citation statements)
references
References 33 publications
24
160
3
Order By: Relevance
“…The solid circles represent the Hugoniot data of Fe 3 C (this work). The open symbols (circle, Sata et al, ; square, Li et al, ; up triangle, Litasov et al, ; down triangle, Ono & Mibe, ) represent the 300‐K isothermal compression data of Fe 3 C. The Hugoniot data (solid diamond; Brown et al, ) and 300‐K isothermal compression data (open diamond; Fei et al, ) of pure iron are also plotted for comparison. The solid and dot lines represent the fitted Hugoniot curve and three‐order Birch‐Murnaghan equation of state curve, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The solid circles represent the Hugoniot data of Fe 3 C (this work). The open symbols (circle, Sata et al, ; square, Li et al, ; up triangle, Litasov et al, ; down triangle, Ono & Mibe, ) represent the 300‐K isothermal compression data of Fe 3 C. The Hugoniot data (solid diamond; Brown et al, ) and 300‐K isothermal compression data (open diamond; Fei et al, ) of pure iron are also plotted for comparison. The solid and dot lines represent the fitted Hugoniot curve and three‐order Birch‐Murnaghan equation of state curve, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The uncertainty in temperature is about 50-200 K estimated from both heating sides. [Fei et al, 2016], which were found to be comparable to pressures within AE2-4 GPa obtained from the measured lattice parameters of B2-KCl using its EoS at 300 K. Because the transparent pressure medium and thermal insulator do not act as a laser absorber, the 300 K EoS has been found to give similar pressures to that of the hot sample in cases where the thermal equation of state of the sample was known [Campbell et al, 2007]. The reported pressures from KCl thus represent a minimum estimate without correction for thermal pressure and may underestimate the pressure by a few GPa [Anzellini et al, 2013].…”
Section: Methodsmentioning
confidence: 99%
“…The uncertainty contributions due to the isothermal EOS parameters V 0 , K T 0 , and KT0 for hcp‐Fe, hcp‐Fe 0.91 Ni 0.09 , and hcp‐Fe 0.8 Ni 0.1 Si 0.1 are found to be of similar magnitude to the uncertainty due to γ 0 and q , which highlights the importance of accurately constraining the parameters V 0 , K T 0 , and KT0 to obtain reliable thermal equations of state. One of the greatest sources of uncertainty is due to the electronic and anharmonic contributions to the thermal pressure, which are not well constrained (e.g., Alfè et al, ; Fei et al, ; Martorell, Vočadlo, et al, ; Martorell, Brodholt, et al, , Martorell et al, ; Moustafa et al, ). To account for this, we enlarge our error bars on density, adiabatic bulk modulus, and bulk sound speed.…”
Section: Extrapolation To Inner Core Conditionsmentioning
confidence: 99%
“…Several general conclusions can be drawn about the c / a axial ratios of pure iron. At 300 K, there is a weak decrease in the axial ratio of iron with pressure (e.g., Boehler et al, ; Dewaele et al, ; Fei et al, ; Steinle‐Neumann et al, ). However, ab initio calculations at 0 K instead show a weak increase in the axial ratio of iron with pressure (Cohen et al, ; Gannarelli et al, ; Steinle‐Neumann et al, , ).…”
Section: Unit Cell Axial Ratio and Anisotropymentioning
confidence: 99%